EFFECTIVENESS OF DATES AND HONEY OF THE FIRST STAGE OF PROLONGED LABOR - Mundarti, (International Journal of Psychosocial Rehabilitation, 2020)
Backgrond The delivery process can lead to prolonged labor elongated influenced by the amount of intake during labor. One of the food sources that contain high calories is dates and honey. High glucose content on a date benefit to labor needed to be straining. Serotonin, tannin and oxytocin helps smooth muscle contraction of the uterus and shortens bleeding time. Besides dates contain oleic and linoleic contribute to the provision of prostaglandins that serve to strengthen and stretch the muscles of the uterus. Honey is fructose and glucose can enter the bloodstream directly, and is a source of instant energy for the body.Purpose The purpose of this research was to determine the effectiveness of dates and honey to the first stage of labor longer active phaseMethods :The study was conducted in Waterford, This study uses a quasi-experimental design Posttest Only Control Group Design. The study population 82 mothers who gave birth in July until November 2019 with a random sample of 72 side which met the inclusion criteriaResults The Provision of dates is very effective in speeding up the opening of the first stage of labor is the active phase as compared to the provision of sugar liquor with a P value: 0.027 (> 0.05). Giving honey is very effective in speeding up the opening of the first stage of labor is the active phase as compared to the administration of fluids with P sugar: 0:03 (> 0.05). Provision of dates is very effective in accelerating the opening stage 1 compared with fluid honey with a P value: 0.008 (> 0.05).Conclusion Expected midwife and patient use of honey and dates instead of sugar to prevent prolonged labor and bleeding